Unconscious in Shakespeare's Plays. - Bergmann, Martin S. (Karnac Books, 2013)
Just as concerts emerge from the interaction of many instruments, so our understanding of Shakespeare is enriched by different approaches to him. Psychoanalysis assumes that creative writers have the need to both reveal and conceal their own inner conflicts in their works. They leave residues in their works that, if we pay attention, can become building blocks that reveal aspects of the unconscious. It is my hope that readers may find that the questions raised add to the pleasure of reading Shakespeare and that they deepens their understanding of his plays. Topics covered include the pivotal p.